Synthesis and Characterization of Ternary BexZn1-xO Nano Thin Films prepared by Pulsed Laser Deposition Technique - Abed, Ali l.; Hussein , Mohammed T. (Iraqi Journal of Physics, 2022)
Beryllium Zinc Oxide (BexZn1-xO) ternary nano thin films were deposited using the pulsed laser deposition (PLD) technique under a vacuum condition of 10-3 torr at room temperature on glass substrates with different films thicknesses, (300, 600 and 900 nm). UV-Vis spectra study found the optical band gap for Be0.2Zn0.8O to be (3.42, 3.51 and 3.65 eV) for the (300, 600 and 900nm) film thicknesses, respectively which is larger than the value of zinc oxide ZnO (3.36eV) and smaller than that of beryllium oxide BeO (10.6eV). While the X-ray diffraction (XRD) pattern analysis of ZnO, BeO and Be 0.2 Zn 0.8 O powder and nano-thin films indicated a hexagonal polycrystalline wurtzite structure. The crystal structure showed a preferential orientation line at (101). Besides the nano thin film Be0.5Zn0.5O has all orientations of ZnO and BeO. Moreover, the calculated average crystallite size for nano thin film was 16.48 nm. The surface morphology of the nano thin films investigated by atomic force microscope (AFM) showed a decrease in the average grain sizes (94.8, 79.2 and 59.4 nm) with the increase of films thickness due to quantum confinement effect.